Integration of Complexed Caffeic Acid into Poly(Lactic Acid)-Based Biopolymer Blends by Supercritical Co2-Assisted Impregnation and Foaming: Processing, Structural and Thermal Characterization - Rodriguez-Mercado, F; Bruna-Bugueno, J; Romero-Figueroa, J; Torres-Mediano, A; Rivera-Fuentealba, P (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Conventional techniques for incorporating active ingredients into polymeric matrices are accompanied by certain disadvantages, primarily attributable to the inherent characteristics of the active ingredient itself, including its sensitivity to temperature. A potential solution to these challenges lies in the utilization of supercritical carbon dioxide (scCO2) for the formation of polymeric foam and the incorporation of active ingredients, in conjunction with the encapsulation of inclusion complexes (ICs), to ensure physical stability and augmented bioactivity. The objective of this study was to assess the impact of IC impregnation and subsequent foam formation on PLA films and PLA/PBAT blends that had been previously impregnated. The study’s methodology encompassed the formation and characterization of ICs with caffeic acid (CA) and β-cyclodextrin (β-CD), along with the thermal, structural, and morphological properties of the resulting materials. Higher incorporation of impregnated IC into the PLA(42)/PBAT(58) blend was observed at 12 MPa pressure and a depressurization rate of 1 MPa/min. The presence of IC, in addition to a lower rate of expansion, contributed to the formation of homogeneous cells with a size range of 4–44 um. On the other hand, the incorporation of IC caused a decrease in the crystallinity of the PLA fraction due to the interaction of the complex with the polymer. This study makes a significant contribution to the advancement of knowledge on the incorporation of compounds encapsulated in β-CD by scCO2, as well as to the development of active materials with potential applications in food packaging. © 2025 by the authors.